International Nurses Day: Nurses can change the world, given the investment and support they deserve. (25th June 2022) - Catton, Howard
Abstract: Every year on International Nurses Day (IND), the International Council of Nurses (ICN) releases a report with resources that can be used by nurses around the world. This year's report responds to the World Health Organization's (WHO) latest strategy for nursing and midwifery, and the findings of the State of the World's Nursing report. In this article, ICN Chief Executive Officer Howard Catton describes the main points of the IND report and recommends that nurses everywhere read it, alongside the WHO strategy, and use that information to increase their knowledge of the global nursing workforce and influence global healthcare policy. It is a toolkit that can assist nurses, other healthcare providers, governments and international organisations to turn global strategy into meaningful local action and improved clinical practice on the ground.